The effect of Gliricidia spp mulching on the growth performance and yield of aerobic rice / Nor Faranadia Samsudin - Samsudin, Nor Faranadia (Faculty of Plantation and Agrotechnology, 2019)
Rice (Oryza sativa L.) is the primary food for majority human in the world and it act as food source. Aerobic rice was produced by MARDI which has the benefit of rapidly growth plant, drought tolerance and improved rice variety under water stress. Therefore, the research studies were conducted to investigate the effect of Gliricidia spp mulching on the growth performance and yield of aerobic rice. It was conducted in the Greenhouse at Uitm Jasin, Melaka in a Completely Randomized Design (CRD). There were two treatments and 5 replications were used. The treatments used were mulching with Gliricidia spp and no mulching. The seedlings of rice were transplanted into pots in 15 days after seeding. Each of the treatments pots were applied with 20 gram of Gliricidia spp mulching. The variety of aerobic rice that has been chosen was AERON 1 and it was taken from MARDI Seberang Prai, Pulau Pinang. Results have showed that the rice with the application of Gliricidia spp mulching had better growth performance upon all parameters consist of plant height, number of tiller and yield attributes. Besides, it showed that the application of mulching on rice can give many benefits to the crop with the results that it has significantly effect on plant growth compare to control treatments.